Corporate Social Responsibility: the Challenges and Constraints - Piasecki, Ryszard; Gudowski, Janusz (Comparative Economic Research. Central and Eastern Europe, 2017)
This article discusses the chances and vulnerabilities of corporate social responsibility (CSR) on two main levels: the small and medium sector at a local level; and big corporations at the macro and international levels. The modern understanding of the definition of CSR is also analyzed. This concept in the management sciences is often misunderstood because it is usually seen as one means in the struggle to achieve a better competitive position. On the other hand, for the development sciences CSR is an effective instrument of income redistribution and as an addition to state support for the underprivileged social groups.